An interactive tool to introduce the waterbed effect. Issue 29 (2015) - Costa-Castelló, Ramon; Dormido, Sebastián
Abstract: Linear control systems are subject to design constraints. Most of these constraints are intrinsic properties of linear systems which can be explained in terms of complex variable theory. In this work a tool designed to introduce the waterbed effect. This tool offers different and simultaneous graphical representations of this effect. All these representations are interactive.